2022
DOI: 10.3126/jnps.v42i1.42662
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perception Regarding Adolescent Sexual and Reproductive Health Services among Adolescents attending a Tertiary Level Hospital

Abstract: Introduction: Adolescence is the transitional phase of growth and development between childhood and adulthood with ages ranging from 10 to 19 years. Adolescent sexual and reproductive health (ASRH) services are the centers where adolescents can get access to their queries regarding health of both physical as well as psychological aspect. The objective of the study was to find out the knowledge and perception regarding ASRH services among adolescents attending a tertiary level hospital. Methods: A descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[4,5] A past study executed among adolescents attending a tertiarylevel hospital noted that 58.0% of the adolescents demonstrated a moderate level of knowledge of sexual and reproductive health. [6] Past studies from Nepal have highlighted that Nepalese adolescents and youth have poor knowledge about sexual and reproductive health. [7][8][9] Poor level of knowledge regarding sexual and reproductive health during adolescence can make them vulnerable to unsafe sex and develop risky sexual behavior in adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5] A past study executed among adolescents attending a tertiarylevel hospital noted that 58.0% of the adolescents demonstrated a moderate level of knowledge of sexual and reproductive health. [6] Past studies from Nepal have highlighted that Nepalese adolescents and youth have poor knowledge about sexual and reproductive health. [7][8][9] Poor level of knowledge regarding sexual and reproductive health during adolescence can make them vulnerable to unsafe sex and develop risky sexual behavior in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 A past study executed among adolescents attending a tertiary-level hospital revealed that 58.0% of the adolescents demonstrated only a moderate level of knowledge about sexual and reproductive health (SRH). 6 Moreover, past studies consistently underscore the inadequate knowledge among Nepalese adolescents and youth regarding SRH practices. [7][8][9] Poor level of knowledge regarding SHR during adolescence can make them vulnerable to unsafe sex and develop RSB in adulthood.…”
Section: Introductionmentioning
confidence: 99%